Optimasi Kekerasan Baja S45C pada Proses Hardening Helical Gear Menggunakan Metode Taguchi - Rikma Mila Ilmaya; Pranowo Sidi; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the uses of steel is as a basic material for making helical gear. Helical gear is made of medium carbon steel S45C which is carbon steel for the use of machine structure. Sometimes in the production process of helical gear has a hardness values that are not in accordance with the standards of hardness that have been determined by the customer. One way to improve the nature of hardness is the hardening process. The hardening process can be done by considering the factors that affected the hardness of a material, such as heating temperature, holding time, cooling medium, and coolant media temperature. In this research, the method of analysis used is Taguchi with signal to noise ratio (RSN) nominal the best to determine the effect of factors and determine the optimal parameter combination in order for knowing the appropriate of hardness value. From the results of research, it is found the factors that influence the hardness of S45C steel in the hardening process of helical gear are the temperature of cooling medium. As for the optimum parameter combination is heating temperature 740oC, holding time 20 minutes, oil cooling medium and coolant temperature 35oC.